Gender, climate change, agriculture, and food security: a CCAFS training-of-trainers (TOT) manual to prepare South Asian rural women to adapt to climate change (Hindi Summary) - Vincent K; Cull, T.; Kapoor A; Aggarwal, Pramod K.; Bhatta, Gopal Datt; Lau, Charlotte; Kristjanson, Patricia M.; Phartiyal P; Parvin G; Bisht S; Nilormee S (2013)
This training-of-trainers manual is designed to train you to be able to deliver a capacity enhancement workshop (CEW) to rural women on climate change and gender. It has been designed by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and is appropriate to the South Asian context.